Decreased expression of alpha-2-HS glycoprotein in the sera of rats treated with Eurycoma longifolia extract - Chen, Yeng; Phang, Wai-Mei; Mu, Alan Kang-Wai; Chan, Choon-Keat; Low, Bin-Seng; Sasidharan, Sreenivasan; Chan, Kit-Lam (Frontiers in Pharmacology, 2015)
Eurycoma longifolia is a Malaysian native herb that has been widely used as an aphrodisiac and a remedy for andropause. Although the physiological effects of the plant extract were predicted as a result of the alterations in protein expression, the key protein(s) involved in these alterations are still unclear. In the present study, we have investigated the effect of standardized Eurycoma longifolia extract on serum protein expression up to 28 days following oral administration in rats. Serum protein profiles were analyzed by 2-dimensional electrophoresis, and altered proteins were identified via mass spectrometry. We observed that alpha-2-HS glycoprotein (AHS) was significantly decreased in the serum of experimentally treated rats compared to controls. Moreover, reduction in AHS was confirmed using competitive enzyme-linked immunosorbent assay. AHS expression is known to be associated with insulin resistance and diabetes. Our data indicated that serum AHS was reduced in rats treated with standardized E. longifolia extract, and therefore form a prelude for further investigation into the effects of this natural extract in animal models involving infertility and diabetes.